Hypohippidium humahuaquense nov. sp. (Ameghiniana, 2013)
Hypohippidium humahuaquense, gen. et sp. nov, (Equidae) is described found in sediments of lower Quaternary age from the Quebrada de Humahuaca, Province of Jujuy, Argentina.